Reduction of supply temperature in existing district heating: A review of strategies and implementations. (1st January 2023) - Guelpa, E.; Capone, M.; Sciacovelli, A.; Vasset, N.; Baviere, R.; Verda, V.
Abstract: Most of the existing district heating systems are second and third generation and operate with supply temperature above 80–100 °C. To meet long-term decarbonization targets, existing networks should be transformed into low-temperature systems in a cost-effective manner. This paper presents a critical review on the strategies that can be adopted to reduce the supply temperature in existing district heating networks taking advantage of previous studies (both research projects and scientific papers) and forerunner experiences. This includes a review of the constraints met during transition and the possible strategies/actions to overcome them, along with the actions to boost the change. The analysis shows that there is often significant room for improvement by exploiting the oversizing of network, substations and terminal units along with techniques, previously adopted with other aims, for a proper infrastructure/operation modification. Temperature reductions can be achieved without groundbreaking infrastructural modifications. Therefore, acting on specific subnetworks (the way usually adopted) is not the only way to proceed; this can be done in entire networks by adopting proper changes of perspective, policies and preliminary analysis. In the meantime, there is still need for specific approaches to estimate the main limitations and the corresponding best actions to implement in a specific network. Graphical abstract: Image 1 Highlights: Strategies to transform existing DH into low temperature systems are reviewed. Experiences, project results, analyses and discussions are included. Limitations due to network, substation and building are taken into account. Possible solutions to overcome the various constraints are reviewed. A possible action plan to implement the transition is proposed.